Pre-operative physiotherapy for elderly patients undergoing abdominal surgery - Rozelle Labuschagne; Ronel Roos (South African Journal of Physiotherapy, 2022)
Background: Elderly patients report a decrease in function and activities of daily living following abdominal surgery. The objectives of our pilot study were to determine the effects of a single pre-operative physiotherapy session consisting of education and exercise on clinical and physical function outcomes in elderly patients.